Consolidation and Transparency : Transforming Tunisia’s Health Care for the Poor - Arfa, Chokri (World Bank, Washington DC, 2013)
Since the 2011 popular revolution in Tunisia, calls for a new social contract have been made to improve social inclusion, including addressing gaps in health care coverage for the vulnerable households. This paper evaluates Tunisia's Free Medical Assistance for the Poor (FMAP) and seeks to identify opportunities to improve universal coverage in Tunisia. The study focuses on the structural and institutional framework of health care coverage for the poor in Tunisia in terms of strengths, weaknesses, and recommendations for achieving universal coverage. The paper reviews Tunisia's health financing and delivery system with a special emphasis on FMAP, and analyzes the main structural and targeting challenges the program faces. The distinctive characteristic of this paper is the focus on institutional design and organizational practice of FMAP. The legal and regulatory framework is assessed in terms of management, beneficiary targeting methods, benefits package, and the information environment. Section 2 provides an overview of health financing and service delivery in Tunisia, including the relationship between the FMAP and the main financing schemes. Section 3 describes key supply-side issues in terms of primary health care provision for the poor. Section 4 assesses the institutional framework of the FMAP in greater detail and its linkages to the health care delivery system. Section 5 focuses on beneficiary selection and targeting methods under the FMAP. Section 6 examines public financial management under the FMAP, which is followed by a discussion in Section 7 of the benefits package. Sections 8 and 9 describe the information environment of the FMAP and how this links to the special focus of future financing reforms. The concluding section discusses the pending agenda and priorities for the FMAP moving forward.